Pengaruh Disiplin Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Dengan Gaya Kepemimpinan Sebagai Variabel Moderasi - Muhamad Nur Sahir; Burhanudin Gesi; Muhran Muhran (Program Studi Manajemen - Fakultas Ekonomi - Universitas Muhammadiyah Kupang, 2019)
The purpose of this study was to determine the effect of workdiscipline and career development, on employee performance withleadership style as a moderating variable. The total sample of 22respondents with the sampling technique using saturated samplingtechniques. The main instrument of data collection is aquestionnaire. Data analysis techniques used multiple regression.The results showed that work discipline had a significant effect onemployee performance but career development had no significanteffect. The leadership style moderates the influence of workdiscipline and performance, thus also the influence of careerdevelopment with performance moderated by the leadership style.